Advances in tumor-associated macrophage-mediated chemotherapeutic resistance in glioma - Liu, Xuebo; Yu, Qi (Frontiers in Cell and Developmental Biology, 2025)
Tumor-associated macrophages (TAMs) are a dominant immune component within the glioma microenvironment and are increasingly recognized as key contributors to therapeutic resistance, the major challenge in glioma management. Understanding their role is critical for developing novel therapies. This review synthesizes current knowledge on TAM-mediated chemoresistance in glioma. TAMs originate from bone marrow-derived monocytes and resident microglia, exhibiting significant heterogeneity and plasticity, particularly between pro-inflammatory (M1) and pro-tumorigenic (M2) phenotypes. M2-like TAMs drive resistance through multiple mechanisms: (1) Modulating drug metabolism/clearance (e.g., via CYP450 enzymes and P-glycoprotein); (2) Secreting protumor factors (TNF-α, ILs like IL-4/IL-6/IL-10, chemokines like CCL5/CCL22, growth factors like VEGF/EGF) that activate survival pathways, induce immunosuppression, promote angiogenesis, and enhance epithelial-mesenchymal transition (EMT); (3) Interacting with glioma stem cells (GSCs) to maintain stemness; (4) Facilitating microenvironmental adaptation (e.g., hypoxia/HIF-1α response); (5) Remodeling the extracellular matrix (ECM) via MMPs, increasing stiffness and impairing drug penetration. Targeting TAMs offers promising approaches to overcome resistance. Strategies include: (1) Reprogramming M2 to M1 phenotypes using agonists (TLR, STING, CD40) or inhibitors (STAT3/STAT6); (2) Metabolic modulation (targeting glycolysis, fatty acid oxidation, glutaminolysis); (3) Blocking recruitment axes (CCL2/CCR2, CSF-1/CSF-1R, CXCL12/CXCR4); (4) Depleting M2-TAMs (e.g., trabectedin, CAR-T cells, M2pep-drugs); (5) Enhancing phagocytosis (anti-SIRPα/CD47, anti-SIGLEC). TAMs are pivotal mediators of chemoresistance in glioma through diverse molecular and cellular mechanisms. Targeting TAM recruitment, polarization, function, or metabolism represents a promising therapeutic avenue. However, the complexity of the glioma microenvironment and blood-brain barrier necessitate combination strategies for clinical translation. Further research is needed to optimize specificity and overcome challenges like compensatory pathways and drug delivery.